Mengembangkan Jiwa Entrepreneurship Perspektif Al-Qur’an - Saputra, Muhammad Nur Adnan (Lembaga Yasin AlSys, 2021)
Indonesia is an Islamic country or a country where the majority of the population is Muslim. There is a lot of negative labeling, such as unemployment, poverty, and low literacy. Especially in the problem of unemployment because of the entrepreneurial spirit that is not widely owned and practiced by Muslims. Islam has taught entrepreneurship through the Prophet Muhammad SAW, entrepreneurship coupled with morals can be a workable solution. This research is library research, data is obtained by reviewing the literature literature. While the analysis uses the content analysis method. The results of the research show that: (1) Al-Qur'an provides several pointers and attitudes to life that should be lived, namely: the suggestion to work as in surah Hud verse 6, and have a broad insight as in surah al-Alaq verse 1-5. (2) There is an intention or desire to do good to fellow humans. No exception in entrepreneurship, where by doing good to others, a good and useful entrepreneurial climate will emerge in the future which has been mentioned in surah al-Hajj verse 77.